2018
DOI: 10.1507/endocrj.ej17-0466
|View full text |Cite
|
Sign up to set email alerts
|

Validation of simple indexes for nonalcoholic fatty liver disease in western China: a retrospective cross-sectional study

Abstract: Abstract. Various noninvasive algorithms have been developed for predicting the presence of nonalcoholic fatty liver disease (NAFLD). The evaluation of the indexes' diagnostic performance has been reported in Europe and Asia over the past decade; however, external validation of them in China is rare. This study was aimed to evaluate various indexes for NAFLD in western China. It was a retrospective cross-sectional study, using data from a large-scale health check-up project at Sichuan provincial hospital. Rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 33 publications
4
23
1
2
Order By: Relevance
“…This potentially could have led to diagnostic misclassification. Validation studies of the FLI in other Chinese populations have reported areas under the receiver operating curve (AUROC) ranging from 0.76 to 0.88, but given that we used a higher FLI cut‐off value than that recommended for the Chinese population, we expect to have smaller misclassification bias. Furthermore, because our study population is relatively ethnically homogeneous (Han Chinese), we anticipate a higher AUROC of the FLI in this analysis.…”
Section: Discussionmentioning
confidence: 98%
“…This potentially could have led to diagnostic misclassification. Validation studies of the FLI in other Chinese populations have reported areas under the receiver operating curve (AUROC) ranging from 0.76 to 0.88, but given that we used a higher FLI cut‐off value than that recommended for the Chinese population, we expect to have smaller misclassification bias. Furthermore, because our study population is relatively ethnically homogeneous (Han Chinese), we anticipate a higher AUROC of the FLI in this analysis.…”
Section: Discussionmentioning
confidence: 98%
“…In addition, this quantitative US model could improve the reliability and reproducibility in comparison with conventional US, when it is standardized by a tissue-mimicking phantom, while these findings are needed to verify in further studies[49]. Above all, US is still recommended for diagnosing moderate and severe steatosis in current guideline[44].…”
Section: Diagnosis Of Nafldmentioning
confidence: 99%
“…It has been validated to a great extent and has been proved to be correlated with insulin resistance, coronary heart disease, and early atherosclerosis [27,28]. Studies have shown that FLI has a moderate discrimination (AUC, 0.83-0.88) in Taiwan, northern and western Chinese mainland [17,29,30]. Our study has testi ed the feasibility of FLI in eastern Chinese mainland and proved that FLI has good applicability in the community population.…”
Section: Discussionmentioning
confidence: 68%
“…ZJU was developed based on BMI, FPG, TG, ALT to AST ratio and gender with an AUC of 0.82 in eastern China, and in the validation cohort using pathological data, the ZJU index had a good accuracy (AUC, 0.896) for the detection of steatosis [15]. Some recent studies have validated ZJU and compared to other models including FLI using large population, with con icting results [29,31]. The underlying reason may be the difference of NAFLD prevalence and characteristics of population.…”
Section: Discussionmentioning
confidence: 99%